Proinflammatory Tear Cytokines in Human Adenoviral Keratoconjunctivitis and Clinical Eye Severity - Santacruz Valdés C; Ponce-Rosas ER; Jimenez-Martinez MC (Clinical Ophthalmology)
Concepción Santacruz Valdés,1 Efrén Raúl Ponce-Rosas,2 Maria C Jimenez-Martinez3,4 1Department of Cornea and Refractive Surgery, Institute of Ophthalmology “Conde de Valenciana”, Mexico City, Mexico; 2Subdivision of Family Medicine, Department of Postgraduates, Faculty of Medicine, National Autonomous University of México, Mexico City, Mexico; 3Department of Immunology and Research Unit, Institute of Ophthalmology “Conde de Valenciana”, Mexico City, Mexico; 4Department of Biochemistry, Faculty of Medicine, National Autonomous University of Mexico, Mexico City, MexicoCorrespondence: Maria C Jimenez-Martinez, Email mcjimenezm@facmed.unam.mxIntroduction: Acute adenoviral conjunctivitis is a disease with mild to severe clinical manifestations. Animal models have provided insight into the role of the innate immune system in clinical damage, but the human immune response at the ocular surface remains poorly understood. Therefore, this study aimed to establish the relationship between tear cytokine levels and disease severity in patients with epidemic keratoconjunctivitis (EKC).Methods: Fourteen consecutive patients with EKC, confirmed with HAdV8 infection, were included. Ocular characteristics were documented, and each patient’s eye was classified as having more or less severe disease. After tear sampling, levels of cytokines IL-8, IL-6, IL-1b, IL-10, IL-12, and TNF-a were measured using a cytometric bead array.Results: Our results showed the expression of proinflammatory cytokines in EKC-affected eyes. IL-6, IL-8, and IL-12 significantly correlated with the total clinical ophthalmological score. In the more severely affected eyes, IL-8 and IL-6 significantly correlated with conjunctival hyperemia, and IL-6 correlated with conjunctival swelling. In the less severely affected eyes, inflammatory response, conjunctival hyperemia, and conjunctival hemorrhages were significantly correlated with IL-12 and TNF-a, and ocular discharge was significantly correlated with all tear cytokines. IL-10 was detected in both eyes, suggesting a possible regulatory counterbalance.Discussion: This study offers novel insights into the pathophysiology of human adenoviral keratoconjunctivitis and its association with clinical data.Plain language summary: Despite the clinical significance of adenoviral keratoconjunctivitis, most studies have concentrated on defining its genotype. Similarly, knowledge of the molecular basis of adenoviral conjunctivitis comes from animal models or cellular lines. Prior to our work, the human immune response at the ocular surface during adenovirus conjunctivitis was poorly understood. Our study described the clinical features of the disease based on severity and found significant correlations between proinflammatory tear cytokines and clinical signs. The results of this study provide new insights into the pathophysiology of adenoviral keratoconjunctivitis and a potential new approach to diagnosis and prompt treatment.Keywords: tear cytokines, adenovirus infection, keratoconjunctivitis, IL-1b, IL-6, IL-8, IL-10, IL-12, TNF-a